Audit of tobacco retail outlets in Hangzhou, China. Issue 4 (16th December 2011) - Gong, Ting; Lv, Jun; Liu, Qingmin; Ren, Yanjun; Li, Liming; Kawachi, Ichiro; ,
Abstract : Objective: To determine the prevalence of tobacco advertisements and warning messages at points of sale as well as to examine the density of tobacco retail outlets in neighbourhoods and around schools in Hangzhou, China. Method: Tobacco retail outlets (n=1639) in all food and tobacco specialty stores were observed objectively by trained students. Tobacco advertisements and warning messages were assessed with an audit, and stores' addresses were recorded with Global Positioning System coordinates. The distances (1) between all pairs of tobacco retail outlets (2) between each tobacco retail outlet and 15 middle schools were calculated to assess the density of tobacco retail outlets in neighbourhoods and around schools. Results: Among the 1639 tobacco retail outlets, <1% had 'no sales to minors' signs, 1.5% had tobacco warning messages, 28% had signs indicating tobacco sale and 12.4% had tobacco advertisements. For 48.7% of tobacco retail outlets, the nearest distances to other tobacco retail outlets were <50 m. For 80% of schools, there was at least one tobacco retail outlets within a 100 m radius. Conclusion: Tobacco advertisement in retail outlets is prevalent and the density of tobacco retail outlets is high in Hangzhou, China. Signs indicating 'no sales to minors' and tobacco warning signs are almost non-existent. These findings point to an urgent need for the enforcement of regulations on display of 'no sales to minors' and a new density standard for tobacco retail outlets based on protecting the public's health.